Structural and Functional Evaluation of Humic Acids in Interaction with Toxic Metals in a Cultivar of Agricultural Interest - Portuondo-Farías, Liane (Revista Ciencias Técnicas Agropecuarias, 2017)
There are plants with the capacity to tolerate stress conditions due to toxic metals by developing mechanisms that allow themto maintain homeostasis. The purpose of this paper was to verify, after the addition of humid acids, as possible stimulators of these mechanisms,the activity of phenylalanine-ammonium-liase and nitrate reductase enzymes, content of total nitrate, proline, (as components both ofthe antioxidant system of bean) as well as nitrogen, in plants subjected to stress by Pb2+. Bean seeds were planted in a typical red Ferralliticsoil, artificially contaminated with 100 mg kg-1 of Pb2+. Fifteen days after germination, the plants were treated with humic acid solutions atconcentrations of 20, 40 and 60 mg L-1 through foliar spraying, on the first and first trifoliate leaves. Every fifteen days enzyme activities wereanalyzed. Results showed a decrease of biochemical-physiological effects caused by Pb2+ in the enzymatic systems of plants treated with humicacids, stating categorically that they may mitigate the stress provoked by metals in the phenological stages evaluated in bean crop, being 40mg L-1 the most prominent dosage.